Prevalence and Associated Factors of Drug-Drug Interactions in Hospitalized Diabetic Patients: A Cross-Sectional Study - Muhammad Adil khan; Nadia Farhanah Syafhan; Retnosari Andrajati; Bambang Wispriyono; Sidra Noor (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Diabetes mellitus is a chronic metabolic condition frequently associated with complications and comorbidities that often require hospitalization for effective management. Such patients are often prescribed multiple medications, which elevate the risk of potential drug-drug interactions (pDDIs). Hence, this study aims to determine the prevalence, severity, common interacting pairs, and factors associated with pDDIs among hospitalized diabetes patients. The study used a retrospective cross-sectional study design conducted at Universitas Indonesia Hospital. LexicompÂ® Lexi-InteractTM software was used to analyze and classify possible drug interactions. Logistic regression analysis was used to identify different factors associated with potential DDIs. Of the 200 patients, 89.0% were observed to have pDDIs. A total of 966 interactions were found, of which 75.6% were moderate, 16.2% were minor, and 8.1% were of major severity. Meanwhile, in the risk rating C category, 71.0% were predominant, followed by B and D, 15.0% and 11.0%, respectively. Multivariate regression analysis showed a statistically significant association of pDDIs with 5â€“8 prescribed medicines (OR=22.8; 95% CI=5.5-94.7; p<0.001), >8 prescribed medicines (OR=64.4; 95% CI=11.3-336.5; p<0.001). The findings of this study revealed that pDDIs are highly prevalent in adult inpatients with diabetes. This emphasizes the critical need for appropriate monitoring and management strategies to reduce pDDIs and their adverse consequences.